Proteção jurídico-ambiental versus desenvolvimento econômico na ocupação de áreas de preservação permanente pelo setor salineiro na Costa Oeste Potiguar: uma abordagem marxista - Pires, Adriana Dias Moreira (2021)
This dissertation aims to contribute to a critical reflection on the existing conflict between the economic development of salt production and the environmental protection of the Permanent Preservation Areas - APP located in the Apodi-Mossoró estuary, based on a Marxist and Marxian theoretical framework. For this purpose, the Marxian categories of work, value and merchandise are used in order to enable understanding of the contradictions involved in the conflict established in the context of salt production in the Rio Grande do Norte. The research was developed from the historical-dialectical materialist method, built by the Marxian social theory, since to achieve the proposed objective it was necessary to use a dynamic and totalizing method of interpretation of reality, so that the conflict established could be seen as part of historical development. The deepening of the critical approach promoted by the thought of Marx and Engels allows us to situate the law as a legal form linked to the commodity form, highlighting its structural limits for the effective preservation of the environment. From there, the criticism admits a demonstration of how the environmental degradation, arising from the crisis of capitalism, is legitimized from legal representations inserted in the field of politics through the State, being the decree of social interest of the salt industry in the West Potiguar an example in this sense. The ecological crisis as a crisis arising from capitalism cannot be understood outside the relations of production and property that found it and, thus, it is understood that the idea of sustainability is not reconcilable with the capitalist market economy, in which both human beings and nature are subject to the condition of commodities. Although the environmental issue cannot be eliminated through the law, it is not possible for us to abolish or not use the law. Therefore, judicialization is presented as a possible tactic for the preservation of APPs in the Apodi-Mossoró estuary. However, there is no way to talk about sustainable development without transforming production relations and overcoming capitalism